Qualitative and Quantitative Analysis of Compounds in Kencur Extract Using TLC and UV-Vis Spectrophotometry - Amarta, Fitri Dwi; Haresmita, Perdana Priya; Eltivitasari, Andita (Jurnal Medika Cendikia, 2024)
Kencur (Kaempferia galanga L.) is one of the plants in the Zingiberaceae family (gingers) that is often used by people in Asia, including Indonesia. Kencur is also widely used as a traditional medicine because it contains active compounds that are beneficial for treatment. This research aims to conduct a qualitative and quantitative analysis of secondary metabolites in Kencur extract samples. Qualitative analysis was conducted using thin layer chromatography with three variations of the mobile phase: Chloroform : Methanol (95:5), Chloroform : Methanol : Glacial Acetic Acid (94:5:1), Chloroform : n-Hexane : Methanol (1:1:0.1), and the stationary phase Silica Gel GF254. Meanwhile, the quantitative analysis was conducted using UV-Vis spectrophotometry at a wavelength of 429.5 nm. The research results show that Kencur contains compounds such as tannins, glycosides, and terpenoids. This research also identifies the presence of curcumin, which has antioxidant effects and other benefits. The results indicate that 2 out of 3 experiments showed positive results, with Kencur containing curcumin at levels of 0.4593% and 0.4393%. The methods used were qualitative methods through thin-layer chromatography and quantitative analysis of curcumin levels in the samples using UV-Vis spectrophotometry.